Pendampingan Menumbuhkan Komunikasi Positif Guru-Murid melalui Mindful Parenting: Sebuah Psikoedukasi di Warraphat School Thailand - Jaro'ah, Siti; Ardelia, Vania; Harita, Adiwignya Nugraha Widhi; Simatupang, Ribka Murtiara; Adani, Erizza Farizan; Sinaga, Renchia; Nirmalasari, Intan; Sholecha, Eka Wiwik S.L. (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
In the educational context, communication problems between teachers and students can have negative impacts. One approach that can be taken to address communication problems is mindful parenting. This community service activity aims to provide mindful parenting psychoeducation to teachers at Warraphat School in Thailand to improve positive communication skills with students. The PKM program was implemented online for teaching staff through counseling and case studies. The psychoeducation results increased teachers' knowledge and understanding of the importance of positive communication and the use of mindful parenting as an alternative method to improve positive communication. The implication of this program is that the implementation of mindful parenting and positive, non-judgmental communication from teachers to students can improve academic achievement